The moral judgement of the child - Piaget, Jean, 1896-1980 (Penguin Books, 1977)
'In this, the most brilliant and persuasive of Professor Piaget's studies of the child's mind, we are led from a consideration of the game of marbles and its rules to a new psychology and a new pedagogy' -New Statesman This pioneering investigation, based on the most meticulous and exhaustive research, sets out to assess the child's maturing sense of what is 'right' and what is 'wrong'. The author is concerned, not with moral behaviour or sentiments, but with moral judgement and the child's idea of justice-as it is revealed spontaneously through children's games-these most powerful social institutions in the life of a child - or through relationships, both with other children and with adults. The Moral Judgement of the Child throws light, not only on child morality, but also in a sense on adult morality; and it addresses a wide and general readership in addition to those involved in the fields of education, medicine, social science and psychology. Jean Piaget is Professor of Child Psychology at the University of Geneva and Director of the International Centre of Genetic Epistemology in Geneva.